2020
DOI: 10.1016/j.clon.2019.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Seven or less Fractions is Not the Standard of Care for Intermediate-Risk Prostate Cancer

Abstract: Evidence is accumulating for seven and less fractions in localised prostate cancer, including one large randomised trial. However, there is much more evidence yet to come and changing practice in advance of this may be premature. We review the reasons to persist with moderate hypofractionation for prostate cancer radiotherapy, until the results of further phase III studies are known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…A state transition model was created to identify the thresholds of complications and costs for MR-Linac to be cost-effective, compared to low-dose-rate (LDR) brachytherapy and EBRT provided in 5, 20 or 39 fractions (common fractionation schedules for localized PCa) [18,24,25]. Our hypothetical cohort consisted of 1000 men with low-and intermediate-risk localized PCa and no other severe comorbidities, treated at age 65 years.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A state transition model was created to identify the thresholds of complications and costs for MR-Linac to be cost-effective, compared to low-dose-rate (LDR) brachytherapy and EBRT provided in 5, 20 or 39 fractions (common fractionation schedules for localized PCa) [18,24,25]. Our hypothetical cohort consisted of 1000 men with low-and intermediate-risk localized PCa and no other severe comorbidities, treated at age 65 years.…”
Section: Methodsmentioning
confidence: 99%
“…This study suggested that MRI-guided radiotherapy can be cost-effective through minor reduction in urinary and bowel complications. This study lacked comparisons with other standard radiotherapy regimens such as brachytherapy and 20-fractions EBRT [12,18,19]. Furthermore, the appraisal of adverse effects did not include sexual complications, which is an important outcome following radiotherapy [20][21][22][23].…”
mentioning
confidence: 99%
“…Professor Loblaw thinks so and articulates why in one half of a pointecounterpoint article [17]. On the contrary, Tree and Dearnaley [18] caution about implementing a new paradigm without waiting for the randomised trials currently maturing. Plenty of mistakes have been made in medicine by shifting practice in advance of robust evidence, as discussed in the article.…”
Section: Clinical Oncologymentioning
confidence: 99%
“…It is well known that there are physical and biological factors that influence the response of tissues from treatment. For example, the uncertainty of the relative and absolute absorbed dose [5], the radiosensitivity, repopulation [1,[6][7][8][9], reoxygenation, repair and redistribution [10]. Furthermore, PCa has been characterized as a tissue with slow repopulation and repair, which is expressed with a low value of α/β ~ 1.5 Gy [11][12][13][14], an interpretation that seems to be incorrect, since the low repopulation does not mean that the temporal dependence in the linear quadratic (LQ) model has to be ignored [1].…”
Section: Introductionmentioning
confidence: 99%
“…In PCa where a low α/β value has been assumed as standard, it is considered that hypofractionation schemes can favor cell death and, therefore, a better local control of the disease. However, recent research points to the need to consider the time factor in the calculation of α/β [1,[6][7][8]15]. In these scenarios, the tolerances and types of tissues located in the treatment area must be considered very carefully, due to the risks of developing further toxicity, as Ferreira's studies show [16].…”
Section: Introductionmentioning
confidence: 99%